Tris(2-ethylhexyl) trimellitate (TOTM) a potential reference fluid for high viscosity. Part I: Viscosity measurements at temperatures from (303 to 373) K and pressures up to 65MPa, using a novel vibrating-wire instrument - Diogo, João C. F. (2015)
The article reports viscosity measurements of compressed liquid tris(2-ethylhexyl) trimellitate or 1,2,4- Benzenetricarboxylic acid, tris(2-ethylhexyl) ester (TOTM) which is an important plasticizer in the polymer industry and has wide applications as a lubricant. Nevertheless, the main motivation for the present work is to propose TOTM as a plausible candidate for an industrial viscosity reference fluid for high viscosity, high pressure and high temperature. This kind of reference fluid is presently on demand by oil industries and the International Association for Transport Properties is developing efforts aiming to select appropriate candidates and to establish the corresponding reference data. The viscosity measurements were performed with a novel vibrating wire sensor. The new instrument was designed for operation at high pressures (up to 100MPa) and temperatures up to 373 K. The present measurements were obtained using the vibrating wire sensor in the forced oscillation or steady-state mode of operation. The viscosity measurements were carried out up to 65MPa and at six temperatures from (303 to 373) K. The viscosity results were correlated with density, using a modified hard-spheres scheme. The root mean square deviation of the data from the correlation is 0.53% and the maximum absolute relative deviation was less than 1.7%. The expanded uncertainty of the present viscosity results, at a 95% confidence level, is estimated to be less than 2% for viscosities up to 68mPa s, less than 2.6% for viscosities between (69 and 268) mPas and less than 3% for higher viscosities. The TOTM density data necessary to compute the viscosity results were measured using a vibrating Utube densimeter, model DMA HP and are described in part II of the present work. No literature data above atmospheric pressure could be found for the viscosity of TOTM. As a consequence, the present viscosity results could only be compared upon extrapolation of the vibrating wire data to 0.1 MPa. Independent viscosity measurements were performed, at atmospheric pressure, using an Ubbelohde capillary in order to compare with the vibrating wire results, extrapolated by means of the above mentioned correlation. The two data sets agree within 1%, which is commensurate with the mutual uncertainty of the experimental methods. Comparisons of the literature data obtained at atmospheric pressure with the present extrapolated vibrating-wire viscosity measurements have shown an agreement within 2% for temperatures up to 339K and within 3.3% for temperatures up to 368 K.